Construction of Cognitive Model of Family Education Decision-Making Based on Neural Network - Wenwen Yao; Ying Zhen; Yu Zhang (Occupational Therapy International)
Family’s academic cognition influences the family’s academic concept, rearing fashion, and academic participation. It is no longer solely associated to kid’s bodily and intellectual development; however, additionally associated to household concord and social progress. With the development of the times, the complicated traits of training proceed to pose new challenges to parents. Exploring the composition and operation mechanism of family training decision-making cognition is envisioned to stop up the key to promote parents’ orderly coaching participation and home university cooperation. However, the associated lookup of usual cognitive mannequin has terrible steadiness and prediction charge in focus results. This paper constructs a cognitive model of family training decision-making principally based totally on neural network. Through the assessment of relevant data, they have an effect of the cognitive model of family coaching decision-making mainly based totally on neural neighborhood evaluated from the accuracy, root suggest rectangular error RMSE, and AUC curve. The experimental effects exhibit that the prediction accuracy of the cognitive mannequin of household training decision-making primarily based on neural community is 15% greater than that of the standard model, and the cognitive balance of the mannequin is 8.2%. This paper demonstrates the effectiveness, feasibility, and practicability of the mannequin in realistic teaching.